“We Will Come to You”: Serving Newcomer Immigrants and English Learners at an AANAPISI Community College - J. Ngo, Federick; Espinoza, Kristine Jan Cruz; E. Lee, David; Teranishi, Robert T. (Innovative higher education, 2025)
Asian American and Native American Pacific Islander-Serving Institutions (AANAPISIs) serve the breadth and diversity of Asian American, Native Hawaiian, and Pacific Islander (AANHPI) students by developing culturally engaging programs, services, and interventions. This case study focuses on how one public 2-year AANAPISI enacted programs to serve recent immigrants in an English for Speakers of Other Languages (ESOL) program, including a novel embedded counseling intervention where counselors visited the same ESOL classrooms several times throughout the semester. We draw upon classroom documentation, student survey data, and interviews with students, faculty, and counselors to understand the challenges reported by students in ESOL programs and to explore how the institution marshaled resources and targeted supports to specifically serve newcomer immigrants and English learner students. ESOL students faced academic and linguistic insecurities, had gaps in college knowledge, and expressed a lack of connectedness to campus. Embedded counseling was a structure that served these students by directly responding to student needs and cultivating relationships between students and key campus staff, thereby fulfilling both the AANAPISI and community college missions of the institution.